A comprehensive look at inflammation in RLS: assessing NLR, MLR, PLR, SII, SIRI, and microR - Kocatürk, İdris; Özen Gökmuharremoğlu, Özge (Journal of Health Sciences and Medicine, 2024)
Aims: Restless legs syndrome (RLS) has been linked to systemic inflammation. The number of studies investigating inflammation in RLS patients is extremely limited. The purpose of this study is to examine the possible role of proinflammatory parameters in RLS, specifically neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), systemic inflammatory response index (SIRI), and microR. Methods: The study included 100 patients admitted to the neurology outpatient clinic diagnosed with RLS using the International Restless Legs Syndrome Study Group ((IRLSSG) scale and 100 healthy controls. Hemogram results were obtained from both RLS patients and healthy controls, while ferritin, folate, vitamin D and B12, and C-reactive protein (CRP) levels were obtained only from RLS patients. Results: The median age of the patient group was 52.50 (43-60.75), while the median age of the healthy group was 51.00 (50-53). The patient group is 37% male, while the healthy group is 34% male. It doesn't vary by age or gender (p=0.658). The two groups showed significant differences in PLR (
Keywords: Restless Legs Syndrome; NLR; PLR; MLR; SII; SIRI; microR; Peripheral Nervous System; Periferik Sinir Sistemi; 3. Good health